The entry and clearance of Ca2+ at individual presynaptic active zones of hair cells from the bullfrog's sacculus. - Issa, N P (1996)
Neurotransmitter is released when Ca2+ triggers the fusion of synaptic vesicles with the plasmalemma. To study factors that regulate Ca2+ concentration at the presynaptic active zones of hair cells, we used laser-scanning confocal microscopy with the fluorescent Ca2+ indicator fluo 3. The experimental results were compared with the predictions of a model of presynaptic Ca2+ concentration in which Ca2+ enters a cell through a point source, diffuses from the entry site, and binds to fixed or mobile Ca2+ buffers. The observed time course and magnitude of fluorescence changes under a variety of conditions were well fit when the model included mobile molecules as the only Ca2+ buffer. The results confirm the localized entry of Ca2+ underlying neurotransmitter release and suggest that Ca2+ is cleared from an active zone almost exclusively by mobile buffer.